2013
DOI: 10.1080/10645578.2013.768072
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Summer Camp Program in China on Children's Knowledge, Attitudes, and Behaviors Toward Animals: A Model for Conservation Education

Abstract: This summative evaluation, conducted in Chengdu, Sichuan Province, China, studied whether participation in a conservation education camp positively changed 8-12-year-old children's (a) knowledge of how to protect animals, (b) care about animals, (c) propensity for environmental and wildlife stewardship, and (d) compassionate behavior toward animals and nature. Influenced by conservation psychology, social learning theory, empathy and moral development, constructivism, and conservation biology, 5-day overnight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…First, these results both add to evidence from the small number of prior studies that have shown knowledge organization change prompted by a brief intervention, and expand upon this evidence by demonstrating knowledge organization change following a real-world, naturalistic learning experience. Second, these results also expand upon evidence about the effects of similar real-world, naturalistic learning experiences, such as a field trip to a museum or zoo (Bexell et al, 2013;Farmer et al, 2007;Gottfried, 1980;Prokop et al, 2007;Randler et al, 2007;Randler et al, 2012;Stronck, 1983). Specifically, this body of research has provided evidence that such experiences can prompt the acquisition of knowledge for individual facts or principles.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…First, these results both add to evidence from the small number of prior studies that have shown knowledge organization change prompted by a brief intervention, and expand upon this evidence by demonstrating knowledge organization change following a real-world, naturalistic learning experience. Second, these results also expand upon evidence about the effects of similar real-world, naturalistic learning experiences, such as a field trip to a museum or zoo (Bexell et al, 2013;Farmer et al, 2007;Gottfried, 1980;Prokop et al, 2007;Randler et al, 2007;Randler et al, 2012;Stronck, 1983). Specifically, this body of research has provided evidence that such experiences can prompt the acquisition of knowledge for individual facts or principles.…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, beyond expanding upon this small body of prior research, it is important to investigate whether naturalistic learning experiences can prompt changes in knowledge organization, and do so over relatively brief timescales. However, prior studies that investigated the effects of naturalistic learning experiences such as a field trip to a museum or zoo (Bexell, Jarrett, & Ping, 2013;Farmer, Knapp, & Benton, 2007;Gottfried, 1980;Prokop, Tuncer, & Kvasničák, 2007;Randler, Baumgärtner, Eisele, & Kienzle, 2007;Randler, Kummer, & Wilhelm, 2012;Stronck, 1983) largely focused on evaluating learning of specific facts (e.g., "Kangaroo rats have giant feet", (p. 172, Gottfried, 1980) rather than changes in in the way that knowledge is organized according to relations among different concepts.…”
Section: Effects Of Brief Learning Experiencesmentioning
confidence: 99%
“…There are suggestions for the inclusion of more hands-on experiments and field trips in future camps. This corroborates previous findings which showed that learning science by doing enhanced students' positive attitude towards science and nature (Birinci Konura, Şeyihoğlu, Sezen, & Tekbiyik, 2011), had positive impact on students' interests toward biology, their career decision and perception concerning biology and daily life (Sezen Vekli, 2013), and promoted positive behaviour toward animals, empathy, and conservation behaviour (Bexell, Jarrett, & Ping, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Knowledge and leadership increase when participants are given time to consider their experiences and contemplate how their lessons fit into the natural world (Bexell, Jarrett, & Ping, 2013). CCNRC incorporates journaling into the camp itinerary to expand campers' writing experiences and allow time for contemplation.…”
Section: Background Of the Color Country Natural Resource Campmentioning
confidence: 99%